2018
DOI: 10.3389/fphys.2018.01234
|View full text |Cite
|
Sign up to set email alerts
|

RXFP1 Receptor Activation by Relaxin-2 Induces Vascular Relaxation in Mice via a Gαi2-Protein/PI3Kß/γ/Nitric Oxide-Coupled Pathway

Abstract: Background: Relaxins are small peptide hormones, which are novel candidate molecules that play important roles in cardiometablic syndrome. Relaxins are structurally related to the insulin hormone superfamily, which provide vasodilatory effects by activation of G-protein-coupled relaxin receptors (RXFPs) and stimulation of endogenous nitric oxide (NO) generation. Recently, relaxin could be demonstrated to activate Gi proteins and phosphoinositide 3-kinase (PI3K) pathways in cultured endothelial cells in vitro. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Authors also demonstrated that the stroke-induced inhibition of endothelial nitric oxide synthesis completely abolished protective effects of Relaxin 20 . Others also demonstrated that effects of both Relaxin-2 and Serelaxin are meditated by their ability to activate eNOS, but not another isoform of the NOS signaling pathway 11,45 . The activation of eNOS is neuroprotective after stroke and, as mentioned above, after GMH 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors also demonstrated that the stroke-induced inhibition of endothelial nitric oxide synthesis completely abolished protective effects of Relaxin 20 . Others also demonstrated that effects of both Relaxin-2 and Serelaxin are meditated by their ability to activate eNOS, but not another isoform of the NOS signaling pathway 11,45 . The activation of eNOS is neuroprotective after stroke and, as mentioned above, after GMH 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated before that compared to relaxin 1 and relaxin 3, relaxin 2 (Serelaxin is an analog of relaxin 2) most effectively produces endothelium relaxation and that this effect is mediated via eNOS pathway 11 . Furthermore, it has been demonstrated that cardioprotective effects of serelaxin following ischemia/reperfusion injury are mediated by eNOS mediated mechanisms 12 .…”
mentioning
confidence: 99%
“…Relaxins are related to the insulin hormone superfamily and proved to have different functional activities on the cardiovascular system. Importantly, relaxins have a strong vasoactive effect, characterized as vasodilation in isolated vessel experiments (Lian et al, 2018). The most potent vasodilatory factor amongst them is RLN2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relevance of PI3Kγ for regulating blood pressure was further demonstrated in normotensive and hypertensive mice using small- molecular inhibitors of PI3Kγ [179]. Recently, relaxin-2, a structurally insulin-related peptide, was shown to exhibit vasodilatory effects on murine mesenteric arteries through a Gα i2 -controlled PI3Kβ-and PI3Kγ-dependent pathway via production of nitric oxide (NO) [180]. Relaxins are implicated in different aspects of the cardio-metabolic syndrome.…”
Section: Biological Functions Of Pi3kγmentioning
confidence: 99%